2014
DOI: 10.1155/2014/678564
|View full text |Cite
|
Sign up to set email alerts
|

The Reasons for Early Weaning, Perceived Insufficient Breast Milk, and Maternal Dissatisfaction: Comparative Studies in Two Belgian Regions

Abstract: Objective and Method. To report on the weaning reasons at the maternity ward, at 3, 6, and 12 months and to report the socioeconomic characteristics of mothers not satisfied with breastfeeding duration as well as of those who have weaned their child because of perceived insufficient milk (PIM). Two cross-sectional studies were performed in 2012. Results. 62.9% of mothers in Wallonia and 56.8% in Brussels are dissatisfied with the duration of breastfeeding. In the two regions, younger mothers, ignoring the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 32 publications
2
23
1
2
Order By: Relevance
“…In the Wallonian context, little adequate BF support exists (except for lactation consultants or limited advice available by phone). In an earlier study, we observed that perceived milk insufficiency, breast engorgement, and cracked nipples accounted for more than 45% of reasons for weaning during the first 3 months (Robert, Coppieters, Swennen, & Dramaix, , ). These issues do require trained personnel, which is scarce in Belgium, (Benahmed, ), as in other countries (Morris, ; Pound, Williams, Grenon, Aglipay, & Plint, ; Sims, Long, Tender, & Young, ).…”
Section: Discussionmentioning
confidence: 97%
“…In the Wallonian context, little adequate BF support exists (except for lactation consultants or limited advice available by phone). In an earlier study, we observed that perceived milk insufficiency, breast engorgement, and cracked nipples accounted for more than 45% of reasons for weaning during the first 3 months (Robert, Coppieters, Swennen, & Dramaix, , ). These issues do require trained personnel, which is scarce in Belgium, (Benahmed, ), as in other countries (Morris, ; Pound, Williams, Grenon, Aglipay, & Plint, ; Sims, Long, Tender, & Young, ).…”
Section: Discussionmentioning
confidence: 97%
“…22,23 Early management of the new breastfeeding mother Some breastfeeding mothers question the adequacy of colostrum feedings and perceive that they have an insufficient milk supply. 24,25 These women may receive conflicting advice about the need for supplementation and would benefit from reassurance, assistance with breastfeeding technique, and education about the normal physiology of breastfeeding and infant behavior. Inappropriate supplementation may undermine a mother's confidence in her ability to meet her infant's nutritional needs 26 and give inappropriate messages that may result in supplementation of breastfed infants at home.…”
Section: Newborn Physiologymentioning
confidence: 99%
“…Only two of them -breastfeeding and vaccination coverage -are measured for young children. According to the 2012 PROVAC survey, 80.9% of mothers breastfeed exclusively when they leave the maternity hospital, with an average duration (exclusive or not) of six months in Brussels [Robert et al, 2014b]. It is slightly higher in the municipalities with a low socioeconomic level, due to the presence of non-Belgian populations where breastfeeding is more common [OSS, 2013b].…”
Section: Salutogenic Factors and Risk Factorsmentioning
confidence: 99%